2021
DOI: 10.1093/jscr/rjab512
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma arising within sciatic nerve endometriosis: a case report

Abstract: Endometriosis is a common condition with significant morbidity. There have been case reports of endometrial deposits affecting the sciatic nerve. Sciatic nerve endometriosis presents with cyclical sciatica and is often difficult to diagnose as it mimics many other causes of sciatica. We report the first case of histological proven endometrial carcinoma arising in a pre-existing sciatic nerve endometriosis. This was initially managed with radiotherapy however symptoms persisted and she opted to have surgery wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Not all cases of sciatic endometriosis can be identified on MRI, and, frequently, further investigations are needed to rule out other potential benign and malignant etiologies. Where there is uncertainty regarding the imaging diagnosis, mainly when differentiating sciatic DIE from malignant peripheral nerve sheath tumors, CT-guided biopsy could be the diagnostic modality of choice [14]. Some authors have reported successfully using high-resolution ultrasound to diagnose endometriosis of the pelvic nerve, which could have potential benefits compared to MRI due to its availability and ease of access [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all cases of sciatic endometriosis can be identified on MRI, and, frequently, further investigations are needed to rule out other potential benign and malignant etiologies. Where there is uncertainty regarding the imaging diagnosis, mainly when differentiating sciatic DIE from malignant peripheral nerve sheath tumors, CT-guided biopsy could be the diagnostic modality of choice [14]. Some authors have reported successfully using high-resolution ultrasound to diagnose endometriosis of the pelvic nerve, which could have potential benefits compared to MRI due to its availability and ease of access [27].…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial and endometriotic epithelial cells also contain various cancer mutations, which may be associated with the formation of pelvic endometriosis or ovarian cancer [13]. Although exceedingly uncommon, instances of carcinoma originating from a localized area of sciatic endometriosis have been documented, exhibiting no notably distinct clinical symptoms compared to noncancerous endometriosis lesions [14], further emphasizing the importance of prompt diagnosis.…”
Section: Introductionmentioning
confidence: 99%